A New Record of Flathead Lobster Thenus indicus Leach, 1816 in Kota Kinabalu, Sabah (Malaysia) Based on Morphology and Genetic Identification, with Global Distribution Checklist: Thenus indicus in Sabah, Malaysia - Radzi, Ihsan Hani; Chen, Cheng-Ann; Hajisamae, Sukree; Daning Tuzan, Audrey; Teng, Sing Tung (Journal of Tropical Life Science, 2025)
Members of the genus Thenus Leach 1816, commonly known as flathead lobsters, are significant contributors to global slipper lobster fisheries.  This study presents the first record of Thenus indicus Leach, 1816 (Crustacea: Decapoda: Scyllaridae) in Kota Kinabalu, Sabah, Malaysia, extending its known distribution to East Malaysia. Prior reports of T. indicus had only been confirmed in Peninsular Malaysia. Species identification was confirmed by mitochondrial DNA cytochrome c oxidase subunit 1 (CO1) sequencing, and morphological examination revealing a lack of spotting on the pereiopods, characteristic setaetion pattern of the second pereiopods, and prominent dentate features of the third maxillipeds. The third pereiopod merus length (ML3) was more than 0.45 times the carapace length (CL), which fulfilled one of the morphometric ratios for identification of this species. Intraspecific p-distances (0.0 – 2.51%, N=10) compared with GenBank reference sequences further validated this finding. A checklist and global map are included to illustrate updated T. indicus distributions. This report enhances the biodiversity and fisheries records of flathead lobsters within Southeast Asia, ensuring better resource management and conservation efforts.